IN-VIVO TOXICITY EVALUATION OF SHILA SINDOOR - Dasari, Srilakshmi; Anand, T.; Khanum, Farhath; Kumar, T. Prasanna; Sreelakshmi, Chaganti (International Journal of Ayurveda and Pharma Research, 2015)
Ayurveda advocates the use of Rasoushadhis (metallic preparations) along with herbal preparations. Unprocessed metals and minerals like mercury and arsenic are highly toxic. Shila Sindoor is one of the Rasoushadhi being possessed with mercury, sulphur and arsenic disulphide as ingredients. In this study 12 rats were selected randomly from stock colony and divided into 2 equal groups of 6 rats each of group-I (vehicle control) and group-II (treatment group). Group-I rats were treated orally with 0.5ml of compound consisting of 3 parts of de-ionized water and 2 parts of honey. Group-II rats were administered with 0.5ml of compound similar to group-I, vortexed with test compound Shila Sindoor (250mg/Kg body weight) for 14 consecutive days to evaluate the toxic effects of Shila Sindoor. There was no morbidity or mortality during the study. Liver and kidney are the two major vital organs to maintain metabolism and protect human body by eliminating the toxins or deposit in these organs to defend other organs of body from toxicity. The results suggested that body weight, 13 different blood parameters like WBC, RBC, platelet count etc., 8 types of biochemical parameters like SGOT, SGPT, creatinine, urea etc., and lipid-peroxidation of group-II were not statistically significant in comparison with group-I. The histopathological study of kidney and liver of both groups revealed normal histology. In this paper genuine effort is put forth to appraise the safety of Rasoushadhis after meticulous process as described in Ayurveda. The result evinced that drug Shila Sindoor is safe for consumption at treatment dose as prescribed in classics.